Alternatives to economic globalization : a better world is possible - Cavanagh, John, 1955-; Mander, Jerry (BK currents book., 2004)
The culmination of a five-year project by the International Forum on Globalization (IFG), this book presents an inspiring plan for moving toward more sustainable, humanistic models of economic prosperity with an emphasis on citizen democracies, local self-sufficiency, and ecological health.